Membangun Keterampilan Menulis Ilmiah Bagi Mahasiswa Tingkat Akhir Melalui Pelatihan Mendeley Reference Manager dan Optimalisasi Metadata Published or Perish - Syuhada, Putri; Fatira AK, Marlya; Gultom, Selfi Afriani; Manik, M. Rikwan E.S; Heddy (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
Mendeley is software that can manage various types of references in writing. The Elsevier company developed this application, which was first launched in August 2008. Mendeley is a reference management software that students need to learn. For every student working on the Final project, it is not only the content of the research that must be considered but also the writing technique. A good final report always includes valid reference evidence. Writing in scientific papers such as the Final Project must follow applicable regulations. In writing the Final Project of Medan State Polytechnic students, especially the Accounting Department, there are still some mistakes in making a bibliography or not citing the source references used in the scientific work. This is due to the lack of student understanding of applications that can be used to facilitate the making of the Final project. Understanding how to write the final report and cite reference sources. To help students facilitate the writing of the final project, it is necessary to have a basic understanding of the applications that can be used. With the Mendeley reference application, which can be used for free, it is hoped that students can apply it to the final project. The result of this service activity is an increase in knowledge, understanding, and proficiency of final-year students of the Accounting Study Program in using Mendeley reference manager for writing their final report. Students find Published or Perish helpful in obtaining metadata and references for their final report.